Moxsha Equipment Rental and Decoration Services Management System - Harini Anandarao; Azizul Azhar Ramli (Applied Information Technology And Computer Science, 2025)
Moxsha Equipment Rental and Decoration Services Management System was developed to overcome the limitations of manual booking and administrative processes used by Moxsha Event, which often resulted in double bookings, scheduling issues, and miscommunication. The primary objective was to design, develop, and test a mobile application for customers and a web-based system for administrators that streamlines rental and decoration services through real-time availability tracking and secure payment features. The project employed the Agile methodology to enable iterative development and stakeholder engagement. Development tools included Flutter, Android Studio, Visual Studio, and a MySQL database. Testing confirmed improved booking accuracy, reduced operational delays, and enhanced customer experience. Key advantages include online payments with automated receipts, effective admin management tools, and simplified return handling. Future work may involve iOS support, integrated chat, advanced customization, delivery tracking, and analytics for decision-making. These improvements position the system as a robust solution for modernizing rental and decoration service operations.